A Survey of Demographic, Professional, and Clinical Characteristics of Clinicians in University Counseling Centers. Issue 2 (30th June 2021) - Newhart, Sean; Pohto, Paul; Mullen, Patrick R.
Abstract : Examining trends in mental health services through periodic surveys can provide a useful overview of a variety of data that can supply researchers, administrators, and practitioners with information that contributes to the building of theoretical frameworks, the creation of practical operating models, and the means to address overarching problems in the field. We collected data on the demographic, professional, and clinical characteristics of a random sample of 205 counselors at U.S. university counseling centers. Findings indicated that participants use diverse clinical approaches and spend the majority of their time providing direct treatment to clients. Implications for practice and future research are discussed.